How Workload and Role Conflict Affect Employee Performance Through Burnout: a Mediation Analysis - Rd. Roro Anggraini Soemadi; Hendra Galuh Febrianto; Mikail Kartaloğlu; Amalia Indah Fitriana; Riski Ulan Sari (Faculty of Economics and Business Udayana University, 2026)
Burnout syndrome, characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment, often arises from excessive workload and unresolved role conflict. This study examines the impact of workload and role conflict on employee performance, with burnout as a mediating variable. A quantitative approach was employed, using questionnaires distributed to service sector employees, and data were analyzed through Structural Equation Modeling (SEM). Results reveal that workload and role conflict significantly and negatively affect employee performance. Both factors also positively contribute to burnout, which in turn reduces performance. The findings confirm that burnout mediates the relationship between workload and role conflict with employee performance. This study highlights the importance of managing workload proportionally and addressing role conflict to prevent burnout. Theoretical contributions enrich human resource management literature, while practical implications provide organizations with strategic insights to design interventions that enhance workplace well-being and sustain optimal employee performance.